Online newspapers business models in spanish scientific journals. A review and suggestions for future research - Goyanes Martínez, Manuel; Peinado Miguel, Fernando (Ámbitos. Revista Internacional de Comunicación, 2019)
Using a hierarchical cluster analysis and a deep literature review of Spanish scientific journals in communication sciences, we identify three themes for understanding online newspapers business models, and three areas that are particularly interesting for future research. First, the need for a better understanding of the concept of business model and an agreed classification on online newspapers. Second, more rigorous and sophisticated statistical methods to study business models on online newspapers and all its levels of analysis, and third, the combination of theoretical frameworks that link management and journalism disciplines.